UZBEK HISTORICAL NOVEL: OYBEK AND QODIRIY (Scientific journal of the Fergana State University, 2025)
The article discusses the emergence of the Uzbek historical novel and the paths of its development. Oybek’s historical novels are compared with Abdulla Qodiriy’s O‘tkan kunlar (Bygone Days). The stylistic peculiarities in the interpretation of the main character in historical novels are analyzed. The distinctive approaches of Oybek and Abdulla Qodiriy in this regard are highlighted.